Ferroptosis in Chronic Liver Diseases: Opportunities and Challenges - Zhou, Xiaoxi; Fu, Yadong; Liu, Wei; Mu, Yongping; Zhang, Hua; Chen, Jiamei; Liu, Ping (Frontiers in Molecular Biosciences, 2022)
Ferroptosis, an iron-dependent non-apoptotic cell death characterized by lipid peroxidation, is a cell death pathway discovered in recent years. Ferroptosis plays an important role in tumors, ischemia-reperfusion injury, neurological diseases, blood diseases, etc. Recent studies have shown the importance of ferroptosis in chronic liver disease. This article summarizes the pathological mechanisms of ferroptosis involved in System Xc−, iron metabolism, lipid metabolism, and some GPX4- independent pathways etc, and the latest research on ferroptosis in chronic liver diseases such as alcoholic liver disease, non-alcoholic fatty liver disease, liver fibrosis, hepatocellular carcinoma, etc. In addition, the current bottleneck issues that restrict the research on ferroptosis are proposed to provide ideas and strategies for exploring new therapeutic targets for chronic liver diseases.